2022
DOI: 10.1002/jbt.23019
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin combats methotrexate‐induced pulmonary fibrosis in rats: Involvement of biochemical and histopathological assessment

Abstract: Polydatin (PD) is a polyphenolic compound found naturally in many fruits such as grapes. It has anti‐oxidant and anti‐inflammatory activities that are of paramount importance for its pharmacological actions. This study aimed to explore possible protective effects of PD against methotrexate (MTX)‐induced pulmonary fibrosis in rats. A single oral dose of MTX (14 mg/kg) per week for 2 weeks caused a significant decrease in glutathione (GSH) content with a marked increase in transforming growth factor‐beta (TGF‐β)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Several studies have confirmed its anti-fibrosis effect by regulating the Cx32-Nox4 signaling pathway (Chen et al, 2020a) and Nrf2-ARE antioxidative pathway (Huang et al, 2015;Gong et al, 2017) in DKD models. PD has also been proved to have protective effects on hepatic fibrosis (Zhao et al, 2017;Li et al, 2018;Lan et al, 2020;Liu et al, 2020;Zhao et al, 2020;Tang et al, 2022), pulmonary fibrosis (Cao et al, 2017;Tang et al, 2019;Zeng et al, 2019;Ali et al, 2022) and myocardial fibrosis (Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed its anti-fibrosis effect by regulating the Cx32-Nox4 signaling pathway (Chen et al, 2020a) and Nrf2-ARE antioxidative pathway (Huang et al, 2015;Gong et al, 2017) in DKD models. PD has also been proved to have protective effects on hepatic fibrosis (Zhao et al, 2017;Li et al, 2018;Lan et al, 2020;Liu et al, 2020;Zhao et al, 2020;Tang et al, 2022), pulmonary fibrosis (Cao et al, 2017;Tang et al, 2019;Zeng et al, 2019;Ali et al, 2022) and myocardial fibrosis (Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Polydatin (PD, C 20 H 22 O 8 ) is a natural active ingredient extracted from the dried rhizomes and roots of Polygonum cuspidatum Sieb. et Zucc., a Polygonaceae plant that plays a protective role in animal models of pulmonary fibrosis (Cao et al, 2017;Tang et al, 2019;Zeng et al, 2019;Ali et al, 2022), hepatic fibrosis (Zhao et al, 2017;Li et al, 2018;Lan et al, 2020;Liu et al, 2020;Zhao et al, 2020;Tang et al, 2022) and renal fibrosis (Huang et al, 2015;Gong et al, 2017;Chen et al, 2020a). Its mechanism of anti-oxidative stress, anti-inflammation, antiferroptosis and regulation of autophagy has also been confirmed by us (Liu et al, 2015;Meng et al, 2015;Meng et al, 2016;Zhou et al, 2022) and other researchers (Gu et al, 2019;Xu et al, 2019;Abd El-Hameed, 2020;Chen et al, 2020a;Fu et al, 2020b;Gao et al, 2020;Han et al, 2020;Sun and Wang, 2020;Deng et al, 2021;Gu et al, 2021) in various kidney disorders.…”
Section: Introductionmentioning
confidence: 99%
“…1 Aroma compounds give fruits their unique flavors, stimulate human appetite, 2 and exhibit pharmacological effects. [3][4][5] The nutritional value and flavor characteristics of fruit aroma compounds enhance their value for various food-related applications. In addition, the types and concentrations of fruit aroma compounds are important indicators for evaluating fruit flavor and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits are rich in nutrients and contain vitamins and trace elements, such as iron, calcium, and phosphorus, that the human body needs 1 . Aroma compounds give fruits their unique flavors, stimulate human appetite, 2 and exhibit pharmacological effects 3‐5 . The nutritional value and flavor characteristics of fruit aroma compounds enhance their value for various food‐related applications.…”
Section: Introductionmentioning
confidence: 99%